A retrospective study of paraganglioma of the urinary bladder and literature review - Zhao, Yi; Zhang, Zhijun; Wang, ShiJun; Wen, Jin; Wang, Dong; Ji, ZhiGang; Zhang, YuShi; Li, HanZhong (Frontiers in Surgery, 2024)
Objective To review and summarize the characteristics and therapy of paraganglioma of the urinary bladder (PUB). Method Patients who underwent the operation in Peking Union Medical College Hospital between January 2012 and December 2021 were reviewed for this retrospective study. Results A total of 29 patients, comprising 9 (31%) men and 20 (69%) women, were included. The main manifestations were hypertension, palpitation, and micturition syncope. Eight patients had an increased 24-h urinary catecholamine, and seven of them had increased norepinephrine. Normetanephrine in seven patients was increased. Six of 18 metaiodobenzylguanidine and 8 of 22 octreotide scans were positive. In total, 15 cases underwent laparoscopic partial cystectomy and 14 underwent transurethral resection of bladder tumor. In all patients, the immunohistochemical index of Melan-A, AE1/AE3, and α-inhibin were negative, and chromogranin A, S-100, and succinate dehydrogenase were positive. The Ki-67 of 28/29 cases was under 5%, and 1 case with a Ki-67 of 20% was diagnosed with malignant PUB. A total of 27 patients had a regular follow-up, 2 patients were lost during the follow-up, 3 patients had a recurrence, and 1 of these patients died within 1 year of surgery. The symptoms all disappeared or were relieved after the surgery. Conclusion The transurethral surgery approach fits PUB tumors with a size <3 cm or that protrudes into the bladder and can significantly reduce the postoperative hospital stay. Early detection and treatment are effective, and regular review is necessary after the surgery.